New Series of Ni(II), Cu(II), Zr(IV), Ag(I), and Cd(II) Complexes of Trimethoprim and Diamine Ligands: Synthesis, Characterization, and Biological Studies - Al-Assafe, Amaal Younis; Al-Quaba, Rana Abdul Malik Sulaiman (Universitas Gadjah Mada, 2024)
New compounds series of [M(TMP)(en)]X·nH2O and [M(TMP)(PD)]X·nH2O, where M = Ni2+, Cu2+, Zr4+, Ag+, Cd2+, TMP = trimethoprim, en = ethylenediamine, PD = o-phenylene and X= Cl− or NO3−, were prepared. The compounds were characterized using techniques including melting points, conductance, elemental analysis, FTIR, NMR, and mass spectroscopy. FTIR spectra indicated TMP acted like a bi-dentate ligand, combining via the nitrogen atoms of azomethine and pyrimidine amino groups. Diamine ligands (en or o-PD) are coordinated via two nitrogen atoms. Prepared compounds showed monomeric behavior and adopted a 6-coordinate octahedral geometry based on magnetic susceptibility and UV spectra. Conductivity measurements revealed Zr(IV) compounds were 1:2 conductive, while Ag+ and Cd2+ were 1:1 conductive; Ni2+ and Cu2+ compounds were non-conductive. Antibacterial tests on compounds and ligands against Bacillus subtilis and Staphylococcus aureus demonstrated broad-spectrum antibacterial activity. The mixed metal compounds revealed an observable tendency of antibacterial activity in the order Zr > Cd = Ag > Cu, making Zr(IV) compounds the most biologically active among them against S. aureus (Gram-positive) while the same compounds showed less antibacterial activity against B. subtilis (Gram-negative) than the free ligand.